The influence of survival conditions on farmer willingness to participate in non-grain conversions of cultivated land based on the SOR model - Hui Fan; JiaXin Liu; Xiaoke Shao; Bingqian Sun; Yilin Yang; Chaoge Shi (PLoS ONE, 2025)
Non-grain conversions (NGC) of cultivated land pose a great threat to national food security, and farmers are the direct actors in the NGC of cultivated land. Exploring the influence of farmer’ survival situation on their willingness to convert cultivated land to non-grain land can provide theoretical support for formulating control policies for NGC of cultivated land. Based on the data obtained from 650 questionnaires in Henan Province and using the SOR model as the theoretical basis, this study explored the impact mechanism of the survival situations of two types of farmers, namely, those with agricultural livelihoods (AL) and those with nonagricultural livelihoods (NL), on their willingness to convert farmland into non-grain land through the use of structural equation models. The results are as follows. The perceived benefits (PB) of NGC can improve their willingness to convert farmland to non-grain land, while the perceived risks (PR) of NGC reduce their willingness to convert farmland to non-grain land. The influence of PB and PR on farmer willingness to engage in NGC of cultivated land in the near term is greater than that in the long term. The influence mechanism of perceived income and perceived risk on the willingness of non-grain conversions of cultivated land varies with the livelihood types of the farmers. The influences of internal family situation (IS) and external family situations (ES) on the willingness to engage in NGC of cultivated land differ according to the types of farmer livelihood. There are differences in the influence mechanism of survival situations on different types of farmers’ willingness to non-grain conversion of cultivated land.